The safety of antiviral therapy and drug withdrawal for the prevention of mother‐to‐child transmission of HBV during pregnancy. Issue 12 (2nd August 2020) - Xiao, Li‐Xin; Chen, Yi‐Ru; Huang, Ping; Mei, Yong‐Yu; Pan, Calvin Q.; Lin, Chao‐Shuang
Abstract: The efficacy of prenatal antiviral therapy (AVT) for preventing the vertical transmission of hepatitis B virus (HBV) is well demonstrated. However, data are limited regarding the safety of postpartum cessation of AVT, which may induce alanine aminotransferase (ALT) elevation. We aimed to investigate the necessity of prolonging maternal AVT after delivery. Chronic hepatitis B mothers at the immune‐tolerant phase with HBV DNA levels >6 log10 IU/mL were prospectively enrolled and received AVT during the third trimester until delivery. Patients were offered to discontinue AVT either at delivery or postpartum week (PPW) 6. In addition, mothers who deferred AVT during pregnancy served as the control group. All mothers were followed until PPW 52 for clinical and virological parameters of hepatitis flares. Among 118 mothers recruited, 91 received AVT with 53 (group A) and 24 (group B) discontinue their treatment at delivery and PPW 6, respectively. Twenty‐seven mothers who deferred AVT during pregnancy were followed as the control (group C). A total of 104 of 118 mothers who completed the study, 50% (52/104) had postpartum‐elevated ALT levels, which were mild and moderate except 6 of 104 (5.77%) of patients had levels ≥5 times the upper limit of normal; 70% (36/52) of the ALT flares occurred within 12 weeks after delivery. In subgroup analyses, the frequency of ALT elevation was similar among the groups A vs B vs C (50.9% [27/53] vs 58.3% [14/24] vs 40.7% [11/27], respectively; P = .447), as well as the mean peak ALT level (108.4/74.1/126.7 U/L in groups A/B/C, respectively; P = .291). Although postpartum ALT flares were common for mothers with or without AVT during pregnancy, most cases of ALT elevation were mild to moderate. Our study observed that extending AVT to PPW 6 did not affect maternal outcomes and ATV should be discontinued at birth. Close monitoring is warranted as severe flares rarely occurred.